2003
DOI: 10.1007/bf02988258
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of treatment effects in brain abscess with positron emission tomography: Comparison of fluorine-18-fluorodeoxyglucose and carbon-11-methionine

Abstract: Positron emission tomography (PET) imaging is in common use preoperatively to clinically evaluate patients who present with central nervous system mass lesions. The usefulness of PET is also recognized as a method to detect intracranial tumorous lesions. A number of papers reportthat some inflammatory processes also showed the uptake of Fluorine-18-Fluorodeoxyglucose (FDG) and Carbon-11-Methionine (Met) tracers. We performed two PET studies before and after treatment in 4 patients with brain abscess. PET showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 9 publications
2
40
0
Order By: Relevance
“…However, due to their limited specificity, additional studies are still necessary to define their precise value in the diagnosis of CNSL. 37,38 Histopathology: Histopathological and immunohistochemical analysis of stereotactic biopsy samples is considered a standard procedure for the diagnosis of PCNSL, 32,39 but is not a routine procedure in patients who already have been diagnosed with DLBCL. Stereotactic biopsy is an invasive procedure, which is of relatively limited sensitivity (20%-65% in immunocompetent patients), particularly in patients treated with corticosteroids.…”
Section: Diagnostic Screening For Cns Disease In Dlbclmentioning
confidence: 99%
“…However, due to their limited specificity, additional studies are still necessary to define their precise value in the diagnosis of CNSL. 37,38 Histopathology: Histopathological and immunohistochemical analysis of stereotactic biopsy samples is considered a standard procedure for the diagnosis of PCNSL, 32,39 but is not a routine procedure in patients who already have been diagnosed with DLBCL. Stereotactic biopsy is an invasive procedure, which is of relatively limited sensitivity (20%-65% in immunocompetent patients), particularly in patients treated with corticosteroids.…”
Section: Diagnostic Screening For Cns Disease In Dlbclmentioning
confidence: 99%
“…Functional imaging using PET is expected to be more sensitive than anatomical imaging such as CT and MRI in detecting abnormalities of the brain; therefore, PET imaging might have a high clinical value in some cases 13) . Several studies have shown high FDG uptake in an abscess 3,4,8,12,15,19,20) . Yamada et al 20) showed that FDG uptake increased in turpentine-induced inflammatory tissue.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that macrophages and neurotrophils in inflammatory tissue utilize glucose as an energy source for chemotaxis and phagocytosis. Although the mechanism of FDG uptake in abscesses remains unclear, it may be related to increased glucose metabolism associated with the inflammatory process and increased cellularity, rather than disruption of the BBB in the brain abscess 19) . Ichiya et al 6) reported that FDG-PET can be successfully used for the detection of infectious lesions as well as in the evaluation of lesion activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations